Transgressão de códigos: elementos estético-semióticos para uma investigação da criatividade em publicidade - Melim, Mauricio José (Universidade do Vale do Rio do Sinos, 2008)
The present study aims at amplifying the debate upon the creativity in advertising, more specifically the kind of creativity recognized in advertisements (not the proposed methods or techniques in order for an ad to become creative, an ordinary issue in advertising manuals). The detection of creativity in advertisements is usually accompanied by words such as ‘original’, ‘astonishing’, ‘intelligent’, ‘outstanding’. The study investigates the phenomenon of creativity in advertising under empirical bases. That is, the aesthetic as proposed by the semiotics serves as the framework for analyzing the data. According to this viewpoint, every aesthetic message conveys mechanisms that transgress the code. The code can be read as imbrications of norms that enable communicative processes to take place. By the exam of this concept (code) will be unrolled elements that will go to hint and to describe some generating mechanisms of creativity in ads
Keywords: código; estética; semiótica; criatividade publicitária; aesthetic; code; semiotic; creativity in advertising; Ciências Sociais Aplicadas